Iekšējās un ārējās vides faktoru nozīme uzņēmējdarbības attīstībā Latvijā - Petrova, Olga (Latvijas Universitāte, 2012)
Bakalaura darba mērķis ir novērtēt uzņēmējdarbības vides faktoru nozīmi uzņēmējdarbības attīstībā Latvijā un izstrādāt priekšlikumus Latvijas uzņēmējdarbības vides uzlabošanai. Bakalaura darbā autore apkopo teorētisko informāciju par uzņēmējdarbības būtību un tās ārējās un iekšējās vides faktoriem, izpēta praktiskās uzņēmējdarbības vides izpausmes un problēmas Latvijā, analizē vietējo institūciju veiktos pētījumus par Latvijas uzņēmējdarbības vidi, kā arī tās vērtējumu starptautiskajos reitingos, izpēta problemātiskākus uzņēmējdarbības attīstību kavējošus faktorus un sniedz priekšlikumus uzņēmējdarbības vides uzlabošanai. Bakalaura darbā tika konstatēts, ka problemātiskāki uzņēmējdarbības attīstību kavējošie faktori Latvijā šobrīd ir liels birokrātijas slogs un nodokļi, un ir jāveic pasākumi situācijas uzlabošanai šajās jomās.

The target of the Bachelor Paper is to find out the significance of internal and external environmental factors for development of entrepreneurship in Latvia and develop proposals for improving business environment in Latvia. In the Bachelor Paper the author summarizes the theoretical information about the essence of the entrepreneurship and its internal and external environmental factors, studies the practical effects and problems of business environment in Latvia, analyzes studies of the Latvian business environment implemented by local institutions, analyzes the assessment of Latvian business environment in international rankings, studies most challenging barriers to business development and finally proposes ways, how to improve business environment. In the Bachelor Paper it was found out that the most problematic factors impending the development of business in Latvia are a large red tape and taxes and measures should be taken to improve the situation in these areas.
Significance of internal and external environmental factors for development of entrepreneurship in Latvia
Keywords: Ekonomika